2006
DOI: 10.1515/multi.2006.017
|View full text |Cite
|
Sign up to set email alerts
|

Negotiation of face in web chats

Abstract: Using conversation analytic methodology, this paper investigates how ‘politeness’ and ‘face’ are negotiated in web chats. Following previous conversation analytic research (Heritage 1984), we first tie the concepts face and social solidarity to the conversation analytic concept of preference organization. We then proceed to describe the system of communication of chats, delineating some technological constraints of the medium that have an impact on the resources available for participants for indicating prefer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(19 citation statements)
references
References 6 publications
0
18
1
Order By: Relevance
“…Politeness can thus be seen as a relational category (Watts 2003) in two senses Ϫ (1) as the discursive organization of social relationship in the sense of orientation to face (Golato and Taleghani-Nikazm 2006;Lerner 1996), marking of stance (Kärkkäinen 2003;Wu 2004), or embodiment of affiliation (Drew 2006), and (2) as an activity-specific and contingent orientation of interactional conduct. In this dual sense of 'relational', politeness can be shown to operate as a participant category.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Politeness can thus be seen as a relational category (Watts 2003) in two senses Ϫ (1) as the discursive organization of social relationship in the sense of orientation to face (Golato and Taleghani-Nikazm 2006;Lerner 1996), marking of stance (Kärkkäinen 2003;Wu 2004), or embodiment of affiliation (Drew 2006), and (2) as an activity-specific and contingent orientation of interactional conduct. In this dual sense of 'relational', politeness can be shown to operate as a participant category.…”
Section: Discussionmentioning
confidence: 99%
“…Although variably referred to as face (Lerner 1996), stance (Kärkkäinen 2004;Wu 2004), social solidarity (Heritage 1984), or affiliation (Drew 2006), CA researchers' distinct perspective on these matters is to analyze them as a participant's concern, located in situated social activities, interactionally occasioned, and publicly available to participants and analysts in the details of interactional conduct. The most fundamental and pervasive interactional resource through which participants orient to relational concerns is preference organization (Boyle 2000;Golato and Taleghani-Nikazm 2006;Heritage 1984;Lerner 1996), a set of methods by which actions are indexed as 'preferred' or 'dispreferred'. Participants orient to preferred actions as the 'interactionally relevant normative structure' (Lerner 1996: 305) by doing such actions without delay or accounts.…”
Section: Politeness In Requestsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, "little is known about the functional range of emoticons" (Vandergriff 2013: 1). Previous research has pointed out to their functions as boosters of group rapport (Derks et al 2008;Golato and Taleghani-Nikazm 2006;Hancock 2004 or Walther andD'Addario 2001), expressions of politeness, e.g. as face-saving strategies (Darics (2010), Golato and Taleghani-Nikazm (2006) or markers of illocutionary force (Dresner and Herring 2010).…”
Section: What Are Emoticons?mentioning
confidence: 99%
“…Prior research has revealed emoticons can also function as face-saving strategies (cf. Darics 2010; Golato and Taleghani-Nikazm 2006;Dresner and Herring 2010). As already mentioned, they can be targeted both at saving the speaker's or the addressee's face, or both simultaneously.…”
Section: Saving Face Strategiesmentioning
confidence: 99%